ENHANCING STUDENTS READING ABILITY THROUGH INQUIRY BASED LEARNING TO EFL STUDENTS - Sari, Farnia (English Community Journal, 2017)
IBT techniques is series of activities that involved maximally throughout the student's ability to search and investigate in a systematic, critical, logical, analytical, so that they can formulate their own discoveries with confidence the search of knowledge and understanding to satisfy curiosity. IBT technique is also supposed to the teachers be creative to set situations. This method used was quasi experimental design. The purposive sampling technique was used on this study. The data were collected by reading test. The collected data was analyzed by using paired sample t-test and independent sample t-test. The results showed that the students reading ability was improved and there was a significant difference between the students who were taught by using IBT and those who were not. With IBT technique encouraged students to take the initiative to have question the phenomenon, to conduct field observations, to analyze the data, and to draw conclusions. Thus, it is to integrate students and synergize various skills of language and different methods.